Brand Böhme: Selling Mystical Texts to Böhme's Audience in Seventeenth-Century Amsterdam. - Pietsch, Andreas (Quaerendo, 2023)
Amsterdam's booming book market famously paved the way for Jacob Böhme's works. Following the success of his Aurora , Janssonius in Amsterdam printed many other works by Böhme around 1640, not least for a German audience. Notably, Janssonius published a whole series of mystical treatises, not only by Böhme, but also by different authors, using Fraktur typefaces and a shared distinctive layout. In his sales catalogue, Janssonius then advertised the whole series as "Böhme's works". Obviously, Janssonius' marketing trick was aimed at selling these books to an audience familiar with Böhme. In line with Andrew Pettegree's compelling analysis of the impact of the book market in forming a "brand Luther" in sixteenth-century Wittenberg, so too can one speak of a "brand Böhme" in seventeenth-century Amsterdam. This article focuses on Janssonius' publishing house and will present new findings concerning books of the mentioned series that have remained unidentified up to now. In doing so, the article focuses on the function of layout and especially the use of Fraktur types in books printed in Amsterdam for a German audience.